2023
DOI: 10.3390/nu15092030
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Bitterness Perception of an Aromatic Myrtle Bitter Liqueur and Bitter Compounds

Abstract: We evaluated sex differences in the perception of bitter compounds and an aromatic bitter herbal liqueur (Mirtamaro) obtained by the infusion of myrtle leaves/berries together with a mixture of Mediterranean herbs/plants as flavoring/bittering ingredients. In a healthy population (n = 231 participants), using bivariate correlations and multivariate linear regression analyses, significant sex differences emerged in quinine bitterness perception, with women showing a higher bitter taste intensity rating than men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(27 citation statements)
references
References 53 publications
(249 reference statements)
0
27
0
Order By: Relevance
“…Their addition in low-salt foods increases food palatability and consumer satisfaction, compensating for salt, fat, and energy reduction [20,23,24]. Moreover, volatile compounds from aromatic plants/herbs have been demonstrated to positively influence the perception and acceptance of bitter taste [25,26]. A recent study showed that the use of various spices and herbs improves COVID-19-induced anosmia and ageusia [17].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Their addition in low-salt foods increases food palatability and consumer satisfaction, compensating for salt, fat, and energy reduction [20,23,24]. Moreover, volatile compounds from aromatic plants/herbs have been demonstrated to positively influence the perception and acceptance of bitter taste [25,26]. A recent study showed that the use of various spices and herbs improves COVID-19-induced anosmia and ageusia [17].…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic bitter herbal liqueurs are constantly dropping their popularity [25][26][27]. Italian "Amari" are alcoholic aromatic liqueurs characterized by a marked bitter taste, generally consumed before or after a meal due to their digestive and tonic-restorative properties [26,28,29].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations